Stock Scalping and Shariah Legitimacy in Modern Capital Markets - Nik Abdul Rahim Nik Abdul Ghani; Hanafi Nazri; Nurul Asikin Binti Abdul Razak (Nusantara: Journal of Law Studies, 2026)
The rapid advancement of financial technology has led to the emergence of various stock trading strategies, including scalping. Scalping is a short-term trading technique in which traders seek to profit from small price movements over very brief timeframes. Due to its fast-paced nature, scalping is often perceived as a high-risk strategy and has raised concerns regarding its compatibility with Shariah principles, particularly in relation to gambling (maisir) and excessive uncertainty (gharar). This study aims to examine scalping practices among stock traders in Malaysia, analyze the associated Shariah issues, and formulate Shariah-compliant guidelines for their implementation. This research employs a qualitative approach, combining content analysis of classical and contemporary Islamic legal sources with field studies involving stock market practitioners in Malaysia. Primary data were collected through in-depth interviews and observations, while secondary data were obtained from scholarly literature, fatwas, and relevant regulatory documents in Islamic finance. The findings indicate that scalping does not inherently involve prohibited elements such as maisir or gharar, if trading decisions are based on adequate technical and fundamental analyses rather than speculative assumptions. The study also finds that profits generated through scalping arise from natural market price movements driven by supply and demand dynamics, which are permissible under Shariah principles. This study contributes to the discourse on Islamic finance and muʿāmalāt by clarifying the Shariah status of scalping practices and offering practical guidance to support Shariah-compliant stock trading in the Malaysian capital market.